Importance of Sustainability Indicators in Construction SSCM - Cataldo, Ieva (Vilnius University Open Series, 2022)
For ongoing review in the strategic planning of the construction industry, numerous complex categories such as ecological, social, and economic are necessary. The present research and analysis look at sustainable supply chain management (SSCM) in the construction industry from a holistic viewpoint, focusing on the construction company's long-term sustainable decision-making tools rather than only SCM for building projects. This article specifies a number of sustainability measures for assessing supplier networks of construction companies. By analyzing their use in prior literature and agreeing to the explanation, those indicators were grouped and assigned to the categories which better reflect the SSCM principle of their application in the construction sphere. For sustainable policymakers and construction business managers, the use of indicators can aid in the development of policies for the construction sector.
Keywords: Supply Chain; Construction; Sustainability Indicators; SCM; Sustainable Construction